Covid-19 Impact on the Music Sector in Belo Horizonte (Minas Gerais, Brazil) - Teixeira, Nísio; Mello Vianna, Graziela; Lima, Ricardo; Jáuregui, Carlos; Furtado, Lucianna; Pereira Alberto, Thiago; Medeiros, Rafael (Frontiers in Sociology, 2021)
This article addresses the difficulties of musicians and measures taken by public and private authorities to mitigate the social impact of Covid-19 in the music sector of Belo Horizonte, capital city of the state of Minas Gerais, Brazil. This is a preliminary result of a research developed by the research lab on Sound, Communication, Textualities and Sociability [ESCUTAS (in Portuguese)] at the Social Communication Department of the Federal University of Minas Gerais. This study has two perspectives. First, we surveyed public sources about Brazilian measures for the sector, as we are interested in verifying policies used by the private and public sectors, not only at the national level, but also at regional (state of Minas Gerais) and local (city of Belo Horizonte) levels. Second, we investigate the impact of the pandemic on the city's music sector, considering various categories of the profession such as composers, interpreters, arrangers, music teachers, DJs, among others.